2011
DOI: 10.1111/j.1468-1293.2011.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of HIV infection among adults in New Zealand: 2005–2010

Abstract: The high proportion of people presenting late reflects inadequate levels of HIV testing. The lower proportion of late presentations among MSM compared with those heterosexually infected may be explained by a higher proportion of recent locally acquired infections together with different testing patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 11 publications
8
36
0
1
Order By: Relevance
“…Our data therefore agree with research concluding that increases in new diagnoses among MSM are unlikely to have been driven by increases in HIV testing alone 4. Diagnosing more incident infections could have reduced the force of infection from undiagnosed HIV infected MSM and helped transmission rates level off, as new diagnoses have done in New Zealand recently, but no change in average CD4 count at time of diagnosis has been recorded among MSM in New Zealand which would indicate this 24. Diagnosing and linking more latent infections into treatment could also reduce the population HIV viral load and contribute to less transmission; approximately 70% of known HIV positive participants in 2011 were currently on ART (unpublished data), but no data on trends of ART uptake have been published for New Zealand.…”
Section: Discussionsupporting
confidence: 87%
“…Our data therefore agree with research concluding that increases in new diagnoses among MSM are unlikely to have been driven by increases in HIV testing alone 4. Diagnosing more incident infections could have reduced the force of infection from undiagnosed HIV infected MSM and helped transmission rates level off, as new diagnoses have done in New Zealand recently, but no change in average CD4 count at time of diagnosis has been recorded among MSM in New Zealand which would indicate this 24. Diagnosing and linking more latent infections into treatment could also reduce the population HIV viral load and contribute to less transmission; approximately 70% of known HIV positive participants in 2011 were currently on ART (unpublished data), but no data on trends of ART uptake have been published for New Zealand.…”
Section: Discussionsupporting
confidence: 87%
“…Using this approach, we obtained results that differ, in many aspects, from those reported in the literature [16,19-23,32,38]. One such discrepancy is the fact that, when analyzing the population-based risk (assessed by late entry rate), we found that, for individuals in the 30–59 year age bracket residing in geopolitical regions with a higher GDP, a decreasing incidence of AIDS, and the highest HIV testing rates, the risk of late entry into HIV care was 35% higher than the national average, despite the lower relative risk and lower proportions of late entry found for that same group.…”
Section: Discussionmentioning
confidence: 71%
“…These findings can be explained by the social and cultural aspects of the AIDS epidemic [13,26] and by the barriers to health care access [18,19,27]. Therefore, late entry into HIV care tends to take on added importance in individuals who are not recognized as being at risk of HIV infection or who do not perceive themselves to be at such risk, such as older individuals [20,21]; individuals in whom the rates of treatment seeking are low, such as men [16,38]; and individuals who are socially marginalized, such as injection drug users [16,19,21]. In Brazil, this inequality is evidenced, in part, by HIV testing rates.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with late presentation in this and previous studies included non-MSMs HIV-exposure group [1],[5],[14],[16],[17],[22], older age [1],[14],[16][19],[23], and non-European origin [14],[17],[19],[22],[24]. Reasons for the increase in late presentation among IDUs in Eastern Europe and heterosexual females and male IDUs from Southern Europe may include suboptimal health care offered to these populations, differences in characteristics that we were unable to adjust for, such as socioeconomic status, the pattern of the underlying epidemic, and appearance of symptoms that may ultimately promote presentation for care [25],[26]. Not all persons recommended for testing undergo testing for a variety of reasons, including stigmatisation, discrimination, criminalisation laws, lack of knowledge, or perceived risk [12].…”
Section: Discussionmentioning
confidence: 98%